Efficacy and Safety of Apatinib for the Treatment of Advanced or Recurrent Cervical Cancer: A Single-Arm Meta-Analysis Among Chinese Patients - Da Huang; Qionghua He; Lingyun Zhai; Jiayu Shen; Fei Jing; Huanhuan Chen; Xiaoqing Zhu; Jianwei Zhou (Frontiers Media S.A., 2022)
Background: Although various effective compounds for the second- and third-line treatment of advanced or recurrent cervical cancer improved the overall survival, the optimal regimen remains controversial. Previous studies revealed that apatinib had extensive anti-tumor activities. However, almost all studies on apatinib in recurrent cervical cancer are non-randomized controlled trials with small sample sizes, different first-line treatments, and uncontrolled statistical analysis, which may result in a lack of effective metrics to evaluate the efficacy and safety of apatinib. Here, this meta-analysis aims to evaluate the efficacy and safety of apatinib in patients with advanced or recurrent cervical cancer.Methods: PubMed, Embase, the Cochrane Library, and Web of Science databases were systematically searched for relevant studies. Outcomes including overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were extracted for further analysis.Results: Seven studies involving 243 patients were enrolled in this meta-analysis. In terms of tumor response, the pooled ORR and DCR were 22.9% and 68.6%, respectively. With regard to survival analysis, the pooled PFS and OS were 5.19 months and 10.63 months, respectively. The most common treatment-related adverse events of apatinib were hand-foot syndrome (all grade: 39.6%, ≥grade III: 7.5%), hypertension (all grade: 34.5%, ≥grade III: 9.2%), and fatigue (all grade: 28.0%, ≥grade III: 5.1%).Conclusions: In summary, this meta-analysis demonstrated that apatinib has promising efficacy and safety for patients with advanced or recurrent cervical cancer.Systematic Review Registration:https://inplasy.com/inplasy-2022-7-0049/, identifier INPLASY202270049